Evaluation of mango loss (Mangifera indica L.) in the retail market of Botucatu-SP - Yalenti Perosa, Jose Matheus [UNESP]; Silva, Cintia de Souza; Arnaldi, Cibele Ribeiro (Soc Brasileira Fruticultura, 2009)
Losses in the mango commercialization process in Brazil has reduced its offer to the consumer. The present study aims at determining these losses in different purchase sites of the retail market, its causes and suggestions for reducing them. Twenty two retail points, including supermarkets, greengroceries and free fair were selected in Botucatu, state of São Paulo, Brazil. The total amount commercialized was 114 ton/year. The following average losses were verified for each mango variety: 'Tommy Atkins'(11, 5%), Haden (12, 4%) and 12, 7% for other varieties. The total loss in retail market reached US$ 25.231,00 corresponding to 14 tons. The average loss percentage observed is compatible with previous studies running in other cities. The results suggest the need of better management, the exposure of the fruit to the consumer, technology in the transportation of the fruits and most appropriate storage for maintaining the quality and the reduction of losses. The results show the need of higher investment in technical personnel reskilling in fruit and vegetable sector.
Keywords: mango; Mangifera indica; losses; commercialization